Mapping Tourists' Information Literacy through the Digital Tourism Services - Prasetyo, Hendi; Irawati, Novi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
Information literacy skills are increasingly important in the digital era, where the internet is very important for obtaining information. Tourists rely on online platforms to plan their trips, search for reviews, and share their experiences. This research aims to determine the level of information literacy skills possessed by tourists. This research uses quantitative descriptive methods. The research results show that Quadrant 1 indicates factors or attributes that are considered important, but information literacy skills in tourism services are not implemented well by tourists. Quadrant 2 reflects factors or attributes that are considered important, and tourist information literacy skills related to these attributes have been implemented well by tourists. Quadrant 3 indicates factors that are considered less important, so information literacy skills in tourism services are not implemented well. Finally, Quadrant 4 describes factors or attributes that are considered less important but are implemented excessively. The research conclusion is that the development of tourism digitalization has been well-received by tourists. The use of digital-based information services, apart from being able to accelerate economic growth, is also able to satisfy the needs and desires of tourists by providing various innovative features, both related to products and other important information needed by tourists. Tourist skills are also increasing with the development of information literacy technology.